Penerapan Arsitektur Hijau Pada Perancangan Rumah Sakit Umum Kelas B Di Kabupaten Blora, Jawa Tengah - Dwiki Nugroho; Karya Subagya (MAESTRO, 2019)
Health is a state of well-being from the body, soul, and social which allows every person to live productively socially and economically. Improvement of health services needs to be supported by providers and health care in a broad sense to the people in need efficiently and effectively. Therefore, it is necessary to support the existence of hospital facilities and infrastructure that support the health system in Indonesia to become more developed. Green architecture is an architectural concept that seeks to minimize the adverse effects on the natural and human environment and produce a better and healthier place of life, which is done by utilizing energy and natural resources efficiently and optimally. 'Green' can be interpreted as sustainable, earthfriendly, and high performance building.